PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB DENGAN METODE FRAMEWORK FOR THE APPLICATION SYSTEM THINKING (FAST) - Fattya Ariani (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2019)
To develop reading interest in school students, the school and library must work together to attract students' reading interest. One of them is by providing a library at school. At present many school libraries for management are still manual, such as starting from recording member data, bookkeeping data to other data storage related to transaction processing to report generation, so it is possible when the process takes place there are errors in recording, lack of accurate reports made and delays in searching required data. In addition the library has operational hours so that few students come. Designing a web-based library information system with the FAST method is the best solution to solve problems that exist in this library. With the FAST method makes system design easier and on target. And with the existence of a website-based library information system increases students' interest in reading because they can access anywhere and anytime without limited time, making it easier for officers to manage library data